iChair - the next generation in intelligent wheelchair mobility / Alif Amirul Faizal … [et al.] - Faizal, Alif Amirul; Ahmad Azizan, Muhammad Firdaus; Juheiri, Muhammad Nurhafiz; Abdul Rahim, Nabil Aiman; Zubaidi, Zhafri Naqiuddin; Mohd Shah, Radziatul Shima (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
An innovative wheelchair, iChair - The Next Generation in Intelligent Wheelchair Mobility solutions has been created to improve mobility and freedom for people with physical limitations who struggle to enter and navigate a variety of surroundings. Traditional wheelchairs frequently have problems, such as limited functionality and user independence, discomfort and lack of ergonomics, safety concerns, and limited assistance from users. Acknowledging these problems, the innovation combines several technologies to overcome these obstacles. It seeks to ensure safety by integrating innovative safety mechanisms to prevent accidents and offer immediate assistance in an emergency. It also aims to promote independence by giving users the ability to perform daily tasks autonomously, such as climbing stairs and reaching objects. Furthermore, the wheelchair incorporates adjustable components and ergonomic elements to improve user comfort during prolonged use. The unique aspect of this solution is how well it integrates Internet of Things (IoT) features, such as GPS navigation for easy route planning, obstacle avoidance and detection for user safety, and fall detection with emergency alerts for prompt help. Furthermore, the automated adjustable seat facilitates customized and ergonomic seating arrangements, and the neck fan adds to user comfort especially in warm regions. There are numerous advantages for society as a whole, including increased safety, comfort, and accessibility for people with physical limitations. This wheelchair solution promotes more inclusion and participation in different facets of daily life by improving mobility and independence, which ultimately contributes to a more accessible and equitable society.